Studies on technical characteristics of the hull forms for traditional fishing boat - Dokanaer Kasto s/o Muning (2014)
This study through compilation of basic hull offsets data by using direct measurement, photographic and flexible wire techniques attempts to investigate the technical characteristics, in particular the hull forms of the traditional boat in K.Terengganu.